Hubungan Indeks Massa Tubuh dan Jenis Pekerjaan dengan Keluhan Low Back Pain pada Buruh Tani Tembakau - Ardelia Faninabilah (Fakultas Kedokteran, 2025)
Low back pain (LBP) is a common health issue among workers, especially agricultural laborers, who often perform physically demanding tasks with nonergonomic working positions. In Indonesia, agricultural workers have the highest prevalence of musculoskeletal disorders, with LBP being the most dominant. This study aimed to examine the relationship between body mass index (BMI) and job type with LBP complaints among tobacco farmers at PT Perkebunan Nusantara X in Jember. The study employed an analytical observational approach with a crosssectional design, conducted from September to December 2024, involving 50 stratified random samples out of 210 farmers working in sorting and fermentation tasks. Data were analyzed using the Chi-Square test. The results showed no significant relationship between BMI and LBP complaints (p-value = 0,491; OR = 1.920), indicating that farmers with high BMI were 1,92 times more likely to experience LBP than those with low BMI, though the result was not statistically significant. However, there was a significant relationship between job type and LBP complaints (p-value = 0,045; OR = 3,273), showing that farmers working in fermentation were 3,273 times more likely to experience LBP than those in sorting. The results of this study emphasized the importance of implementing effective ergonomic interventions to reduce the risk of low back pain (LBP) and support improved worker health and productivity.
Entry oleh Arif 2026 Maret 26
Keywords: Low Back Pain; Body Mass Index; Job Type; Tobacco Farmers; Ergonomic Risks; Musculoskeletal Disorders